Outcome of orbital decompression for disfiguring proptosis in patients with Graves' orbitopathy using various surgical procedures. Issue 11 (21st November 2008) - ; Mourits, M P; Bijl, H; Altea, M A; Baldeschi, L; Boboridis, K; Currò, N; Dickinson, A J; Eckstein, A; Freidel, M; Guastella, C; Kahaly, G J; et al.
Abstract : Aim: To compare the outcome of various surgical approaches of orbital decompression in patients with Graves' orbitopathy (GO) receiving surgery for disfiguring proptosis. Method: Data forms and questionnaires from consecutive, euthyroid patients with inactive GO who had undergone orbital decompression for disfiguring proptosis in 11 European centres were analysed. Results: Eighteen different (combinations of) approaches were used, the swinging eyelid approach being the most popular followed by the coronal and transconjunctival approaches. The average proptosis reduction for all decompressions was 5.0 (SD 2.1) mm. After three-wall decompression the proptosis reduction was significantly greater than after two-wall decompression. Additional fat removal resulted in greater proptosis reduction. Complications were rare, the most frequent being worsening of motility, occurring more frequently after coronal decompression. The average change in quality of life (QOL) in the appearance arm of the GO-QOL questionnaire was 20.5 (SD 24.8) points. Conclusions: In Europe, a wide range of surgical approaches is used to reduce disfiguring proptosis in patients with GO. The extent of proptosis reduction depends on the number of walls removed and whether or not fat is removed. Serious complications are infrequent. Worsening of ocular motility is still a major complication, but was rare in this series after the swinging eyelid approach.